Improving Al-Qur'an Literacy: CTL Model, Digital Al-Qur'an, and Short Surah Reading Skills in PAI Learning - Mustika Rini, Ayu Wardani (Program Pasca Sarjana, Universias PGRI Argopuro Jember, 2024)
The purpose of this study was to improve the Short Letter Reading Skills through Digital Qur'an and overall student learning outcomes. The role of PAI teachers in the use of the CTL (Contextual Teaching and Learning) model shows the importance of the real context according to the situation in the environment by the students themselves in identifying problems in life so that the concepts received by students are more meaningful. This research is in the form of a quantitative experiment with the research subjects of 8th grade students of MINQU Gumukmas Junior High School in Gumukmas-Jember, academic year 2023/2024. The data in this study are quantitative data obtained from tests of students' knowledge and understanding through questionnaire tests. The results of the percentage of success of this study show: (1) the effect of the CTL (Contextual Teaching and Learning) Model on improving students' Short Letter Reading Skills through Digital Al Qur'an was 83.2%, (2) the effect of the CTL (Contextual Teaching and Learning) Model on improving students' PAI Learning Outcomes was 72.5%, and (3) the effect of the CTL (Contextual Teaching and Learning) Model on improving Short Letter Reading Skills through Digital Al Qur'an and students' Learning Outcomes together was 84.2%. This means that the application of the CTL (Contextual Teaching and Learning) Model in improving Short Letter Reading Skills through Digital Al Qur'an and Student Learning Outcomes has a significant effect